An integrated assessment of alternative land-based passenger transport policies: A case study in Tenerife. (July 2016) - Hernández González, Yeray; Corral Quintana, Serafín
Highlights: Integrated assessment approach was applied to understand transport policy alternatives. Social techniques to identify relevant stakeholders becomes relevant when dealing with governance issues. Transport policy alternatives should be proposed and discussed together with stakeholders. Stakeholders' positions about the transport issue influence decision-making processes. Abstract: Over recent decades, there have been numerous cases of land-based transport policies that have lacked clear and coherent strategies. This has not only hampered the resolution of issues like road congestion, but has also created new ones (e.g. strong social opposition to new train infrastructures). The absence of such strategies highlights the need for long-term transport policies with a wider vision of the issues, since land-based transport cannot be considered from just a technical perspective. The main objective of this article is to implement a participatory integrated approach to facilitate the understanding of land-based passenger transport governance issues on Tenerife, in the Canary Islands. Relevant policy issues and alternatives are identified by the stakeholders involved. The inclusion of stakeholders in the assessment process is crucial to frame transport governance issues appropriately and to define and assess plausible policy alternatives. This assessment process even included a final step of validation of the results by stakeholders to foster discussion among them about transport issues and policy alternatives. Finally, due to the obstructive role played by some stakeholders in influencing past transport policies, an analysis of possible coalitions among stakeholders is also discussed.